Social support, social interaction and vocational studies role on youth leadership skills among polytechnic students in Lagos State, Nigeria - Yusuf, Sodiq Adewale; Daud, Mohd Najmi; Arshat, Zarinah; Abdul Ghani, Mohamad Salleh; Obiora, Emeka Chike (Human Resource Management Academic Research Society, 2024)
Half of the world's population is under 30 years, therefore developing leadership skills is essential for young people to thrive and make a difference. Youth’s leadership has received growing attention as a way of preparing young people to contribute meaningfully to society. Ultimately, it is necessary to consider involving young people in development initiatives. Consequently, the next generation will have more opportunities to prepare for leadership roles and serve their country. But there are a lot of obstacles that prevent young people from developing their leadership abilities, and these obstacles can differ from one region to another. This study used 381 Lagos State Polytechnic students to evaluate how social support, social interaction, and vocational studies affect youth leadership skills. Samples were selected using multistage random sampling. Pearson correlation was used to test the hypotheses at a significant level of 0.01. The study found that vocational proficiency best predicts leadership potential. It is proposed that leadership qualities should be incorporated into the standard curriculum of schools. Therefore, as part of their normal coursework, students should be provided with opportunity to practice leadership abilities.